Pengembangan E-LKPD Energi Dan Usahaberbasis React Untuk Meningkatkan Literasi Digital Siswa SMK - Abrila Zahrotus Sufia; Ahmad Khoiri; Siti Lailiyah (CV. ITTC INDONESIA, 2025)
been fully accompanied by an increase in students’ digital literacy, especially at the vocational high school (SMK) level. This study aims to develop a digital student worksheet (E-LKPD) on Work and Energy based on the REACT (Relating, Experiencing, Applying, Cooperating, Transferring) model to enhance students’ digital literacy. The research employed the ADDIE (Analyze, Design, Development, Implementation, Evaluation) development model. The sample consisted of grade X AKL 3 students selected through purposive sampling. Research instruments included validation sheets, practicality questionnaires, tests, and digital literacy questionnaires. Validation results showed that media experts rated the product at 4.84 (96.84%) and subject matter experts at 4.45 (89%), both in the